2021
DOI: 10.1002/mds.28804
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic AOPEP Loss‐of‐Function Variants Cause Progressive Dystonia with Prominent Limb Involvement

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…7 No other de novo class IV or V variant was identified in this cohort. The TMEM151A mutation was identified in one of 23 patients of our PRRT2negative PKD cohort, which is in accordance with the frequency of 4.8% found by Tian et al 1 We report on a de novo mutation in TMEM151A in a patient with PKD. Our findings confirm TMEM151A variants as a genetic cause of PKD and suggest that de novo mutations in this gene are infrequently responsible for…”
Section: De Novo Mutation In Tmem151asupporting
confidence: 92%
See 3 more Smart Citations
“…7 No other de novo class IV or V variant was identified in this cohort. The TMEM151A mutation was identified in one of 23 patients of our PRRT2negative PKD cohort, which is in accordance with the frequency of 4.8% found by Tian et al 1 We report on a de novo mutation in TMEM151A in a patient with PKD. Our findings confirm TMEM151A variants as a genetic cause of PKD and suggest that de novo mutations in this gene are infrequently responsible for…”
Section: De Novo Mutation In Tmem151asupporting
confidence: 92%
“…An athetotic component was observed as well. Similarly to proband 3 reported by Zech et al, 1 carrying the identical p.Ala234Serfs*5 change in a homozygous state, he reported that dystonia improved when he had time to relax with symptoms completely subsiding. By sitting with the back against the wall, the retrocollis could be antagonized.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The disease course is progressive and speech articulation difficulties, muscle cramping and pain, orofacial dyskinesia, and swallowing dysfunction were described. In a French family, late onset parkinsonism with prominent bradikynesia, dysarthria, and frequent falls was described [117].…”
Section: Autosomal Recessivementioning
confidence: 99%